MORPHOLOGICAL CHARACTERISTICS OF NORMAL TENDINOUS CORDS OF ATRIOVENTRICULAR HEART VALVES OF FETUSES, NEWBORNS AND INFANTS - Федонюк, Л.Я.; Пентелейчук, Н.П. (World of Medicine and Biology, 2014)
Background. Many fundamental works both of Ukrainian and foreign authors are devoted to the description of the heart valve apparatus, although still there is a number of unknown questions connected with age peculiarities of the structure of its components: cusps, papillary muscles and tendinous cords. Considering the fact that the valve apparatus possesses a big functional exertion and changes with time, learning individual changes of the heart valve apparatus and its components is of great importance. Objective of the work was to study the morphological structure and polarization properties of the atrioventricular heart valves tendinous cords of fetuses, newborns and infants using macroscopic, microscopic, histochemical, immunohistochemical, electron microscopic, statistical methods, and method of laser polarimetry and 3D modeling method.Materials to study of mitral and tricuspid valves tendinous cords were conducted on 186 atrioventricular valves of the heart, taken from the hearts of 40 fetuses (13-40 weeks of the prenatal period of human ontogenesis 85,0-370,0 mm parietal-coccygeal length), 26 infants (from birth to 28 days of life) and 27 infants (29 days to 1 year) who died from causes not associated with pathology of the cardiovascular system.Results. As a result the macroscopic study indicates that cusps of the mitral and tricuspid heart valves associated with papillary muscles by tendinous cords, which have the form of thin fibrous strands. Cusps tendinous cords of the mitral valve anterior cusp is represented by two types of tendinous cords: of a thickened zone and supporting. Cusps tendinous cords of the mitral valve posterior cusp is represented by three types of tendinous cords: of a thickened zone, dividing rear wing and basal. In tricuspid valve observed five types of tendinous cords: fan, of free edge, thickened areas, deep and basal.The number of tendinous cords of a newborn 2.5 times the number of tendinous cords in fetus and tendinous cords of infants exceed the number of tendinous cords of newborn 1.07 times. The length of the atrioventricular valves tendinous cords in newborns in 1.02 times the length of the tendinous cords in fetuses, and the length of the tendinous cords in infants at 1.16 times the length of the tendinous cords in newborns.3D modeling of the tendinous cords of the fetal hearts (90,0 mm parietal-coccygeal length) detected that papillary muscles pass directly to the cusps of the atrioventricular valves.By light microscopy established that in the fetus of 125,0 mm parietal-coccygeal length between papillary muscles and cusps of the atrioventricular valves are observed primary tendinous cords in the form of thin strands. Primary tendinous cords formed by a layer of dense packed cardiac muscle cells and a small number of mesenchymal cells. The examinations conducted by means of electron microscopy showed that the base of the tendinous cord includes fibroblasts and fibrocytes. The base of the tendinous cords of fetuses and newborns is composed of directed bundles of collagen fibers and bundles of cardiac muscle cells.Immunohistological examination of the tendinous cords found a positive reaction: Anti-Human Collagen IV+, which indicates the presence of collagen IV in the basal membrane of cardiac muscle cells.The optical properties of the tendinous cords of mitral and tricuspid heart valves provide an opportunity to differentiate the collagen, elastic and muscle fibers in their structure, confirming type of the tendinous cord.Conclusion. Thus, the results of the study showed that the tendinous cords of the fetuses, newborns and infants have a type of connective tissue fibers extending from the apex of the papillary muscles and fixed to the cusps of the atrioventricular valves of the heart. The ratio of tendinous cords in fetuses, newborns and infants, which are fixed to the cusps of the mitral and tricuspid heart valves, respectively, is 1.5:1. In males, the length of the tendinous cords is greater than that of females in all three age groups.Three-dimensional computer reconstruction of the tendinous cords of the fetus heart 90,0 mm parietal-coccygeal length demonstrate their absence. Reconstruction model of the heart valve apparatus of fetuses of 135,0 mm parietal-coccygeal length show that between papillary muscles and cusps of the atrioventricular valves of the heart are observed newly formed tendinous cords in the form of a thin single strands. Method 3-D reconstruction of the tendinous cords of the mitral and tricuspid heart valves of newborn children shows that their base is formed by the central located collagenous core and periphery located loose connective tissue, which contains blood vessels.The examinations of the tendinous cords conducted by means of microscopic and submicroscopic methods showed that tendinous cords of fetuses belong to the fibro-muscular type, newborns - to fibro-muscular and fibrous types, infants - fibrous type, which is confirmed by the optical properties of the tendinous cords specific laser polarimetry.
Keywords: tendinous cords; papillary muscles; mitral valve; tricuspid valve; fetus; newborns; infants